2013
DOI: 10.1083/jcb.201207142
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt signaling inhibits osteoclastogenesis independent of osteoprotegerin

Abstract: Canonical Wnt signaling through Fzd8 and β-catenin negatively regulates osteoclast differentiation and reduces bone resorption independent of osteoprotegerin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
126
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 39 publications
6
126
0
Order By: Relevance
“…S2). This is striking given that canonical Wnt signaling inhibits osteoclast differentiation and promotes osteoblast-mediated inhibition of osteoclastogenesis (Albers et al , 2013; Glass et al , 2005; Spencer et al , 2006). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). This is striking given that canonical Wnt signaling inhibits osteoclast differentiation and promotes osteoblast-mediated inhibition of osteoclastogenesis (Albers et al , 2013; Glass et al , 2005; Spencer et al , 2006). …”
Section: Resultsmentioning
confidence: 99%
“…Loss of β-catenin in mesencymal progenitors and inactivation of Lrp5, one of the Wnt coreceptor, prevents osteoblast differentiation resulting in low bone mass (Gong et al , 2001; Kato et al , 2002). Moreover, Wnt activation in differentiated osteoblasts promotes the ability of osteoblast to inhibit osteoclast differentiation and their activity (Albers et al , 2013; Glass et al , 2005; Spencer et al , 2006). Disruption of the well-tuned balance of the production of bone matrix by osteoblasts, and the resorption by osteoclast causes disorders such as osteoporosis (Baron and Kneissel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have shown that Ifrd1 deficiency attenuates the interaction between ␤-catenin and HDAC1, subsequently increasing the acetylation of ␤-catenin at K49 and leading to accumulation in the nucleus and activation of ␤-catenin-dependent transcription of Opg in osteoblasts (10). ␤-Catenin controls osteoclastogenesis (37,38); thus, it would be worth investigating whether Ifrd1 controls osteoclastogenesis by regulating ␤-catenin-dependent transcription, as observed in osteoblasts.…”
Section: Discussionmentioning
confidence: 97%
“…Wnt3a is known to play a critical role in the skeletal system, including in inflammatory processes, bone formation, and bone resorption [10,11,18,19]. In particular, Wnt3a is an important responder to mechanical stimulation by activating canonical Wnt signaling [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Although the involvement of Wnt/β-catenin signaling in osteoblast development has been characterized [2,4,9], the role of Wnt3a in the regulation of bone-resorbing osteoclasts is not fully understood. While some have reported that Wnt3a attenuates osteoclast development [10,11], others have found that it has little effect on osteoclastogenesis [6]. Using both mouse bone marrow cells and RAW264.7 pre-osteoclast cells, we examined the effects and regulatory mechanism of Wnt3a-driven regulation of osteoclast development.…”
Section: Introductionmentioning
confidence: 99%